DEVELOPMENT MEASURES TO ENHANCE THE ECOLOGICAL SAFETY OF SHIPS AND REDUCE OPERATIONAL POLLUTION TO THE ENVIRONMENT - Oleksiy MELNYK; Svitlana ONYSHCHENKO; Oleg ONISHCHENKO (Scientific Journal of Silesian University of Technology. Series Transport)
Reduction of ecological risks of shipping is a challenging task that requires methods of legislative and regulatory control, organizational measures, and technical and technological support. Furthermore, the matter concerns not only the reduction of possible risks but also the level of existing impact on the marine environment because of exhaust gas emissions by ships, discharge of waste and ballast water, as well as control of ecological consequences of accidents. The purpose of this study is to analyse possible sources of environmental impact during ship operation cycles, identify significant risks, review existing potentials to reduce the risk of ship accidents and their environmental consequences, and develop solutions to existing problems. This study offers results, which can serve as the initial basis for the formation of comprehensive measures on the reduction of environmental risks, and consequences of possible accidents for the environment caused by ships and international shipping.